ANALISIS PUISI “HATIKU SELEMBAR DAUN” KARYA SAPARDI DJOKO DAMONO DENGAN PENDEKATAN EKSPRESIF - Hasanah, Uswatun; Nisa, Khairun; Septiawan, Habi (Laboratorium Pembelajaran Bahasa, FKIP Universitas Lampung, 2024)
The expressive approach is one of the approaches that can be used to study a literary work. The expressive approach is an approach that focuses on the author of a literary work. The author is a very important thing in a study with this expressive approach, because what will be studied is the relationship between an author and his creations. In this study, the author will discuss the results of the study of the poem entitled